Antimicrobial Sysceptibility Pattern of Enteropathogenic Escherichia coli (EPEC) in Paediatric Diarrhoeal Patients - Shimu Saha; Sanya Tahmina Jhora; Tanjila Rahman (IMC Journal of Medical Science, 2014)
Enteropathogenic Escherichia coli (EPEC) mediated infantile diarrhoea among children is an important cause of morbidity and mortality in developing countries. The antimicrobial susceptibility pattern of EPEC strains isolated from children under 5 years of age was studied. Stool samples from 272 patients with diarrhoea were collected from two tertiary care hospitals. Out of 272 stool samples, 20 (7.35%) isolates were identified as EPEC on the basis of presence of bfpA gene detected by polymerase chain reaction and antibiotic susceptibility testing was performed on these EPEC strains by Kirby-Bauer disc diffusion method. The antimicrobial susceptibility test revealed that the EPEC isolates were highly resistant to ampicillin (100%), nalidixic acid (95%) and tetracycline (95%) and were sensitive to ceftazidime (95%), cefotaxime (90%), ceftriaxone (95%), imipenem (100%) and levofloxacin (85%). Isolation of EPEC is of great importance since they are responsible for acute diarrhoeal diseases in large number of children under the age of five years. The high antimicrobial resistance observed in our study indicates indiscriminate or improper use of antimicrobials, besides the risks of self-medication.